New constant modulus algorithm suitable for nonconstant modulus signals - RAO Wei1; SUN Hui1; GUO Ye-cai2; DENG Cheng-zhi1; WANG Sheng-qian1; TIAN Wei1 (Tongxin xuebao)
The steady-state mean square error（MSE） of constant modulus algorithm（CMA） can not converge to zero for nonconstant modulus signals.By changing the multimodulus of nonconstant modulus source to single modulus,a new cost function was defined.And the new CMA based on such cost function can lead the steady-state MSE to zero.Theoretic analysis and computer simulation results demonstrate that the proposed algorithm offer high performance.